Proteinuria, Hypoalbuminemia, and Chronic Lymphocytic Leukemia: An Unusual Trio - William Wung MD; Shubha Ananthakrishnan MD; Brian A. Jonas MD (SAGE Publishing, 2018)
Chronic lymphocytic leukemia (CLL) is a chronic, progressive lymphoproliferative disorder characterized by a monoclonal population of functionally incompetent lymphocytes. Renal involvement is rare and poorly described. A 57-year-old male with no prior medical history was diagnosed with CLL and followed with a watch and wait approach. He was referred to our institution several months later due to concern for Richter's transformation to diffuse large B-cell lymphoma. A positron emission tomography/computed tomography scan showed no evidence of diffuse large B-cell lymphoma; however, the patient was noted to have hypoalbuminemia, nephrotic range proteinuria, an acute left renal vein thrombus, and a right pulmonary embolus. A nephrotic syndrome workup including autoimmunity and infection was unremarkable, and a kidney biopsy was deferred due to concern for renal compromise in the setting of a renal vein thrombus. The patient was treated with 6 cycles of reduced-dose fludarabine, cyclophosphamide, and rituximab for a presumed CLL-associated nephrotic syndrome and anticoagulation for his venous thromboemboli. At 6-month follow-up, the patient achieved complete remission of his CLL with normalization of all cell lines and resolution of his nephrotic range proteinuria. Repeat computed tomography scans showed no evidence of recurrent venous thromboemboli. This case demonstrates a potential role of empiric chemotherapy in cases of CLL-associated nephrotic syndrome given its potentially life-threatening sequelae and response to treatment.